Editorial - Kristy L Archuleta; John E Grable (Journal of Financial Therapy, 2011)
The Journal of Financial Therapy continues to garner national and international attention. This is largely due to the excellent submissions received and the outstanding work of the editorial board and reviewers. Although the Journal is just beginning its second year, papers from the past and current issue have been quoted in the media, on the Internet, and in college classrooms. A simple Google Internet search of the phrase “financial therapy” leads those navigating the World Wide Web directly to the Journal. In conjunction with New Prairie Press, papers, reviews, and profiles are accessible to anyone in the world via the open access journal network, which makes it highly likely that authors will be referenced in additional manuscripts. It is definitely an exciting time to be involved in the development of financial therapy as a new field of study through the Journal.
Keywords: Financial Therapy